Association Between Religion and Suicidal Behaviors in Cancer Patients (2017)
Background Whereas most studies have focused on how the religious beliefs positively interfere with the presence or execution of suicidal behaviors, few have identified differences among religious beliefs and how these can not only be consider as a protective factor for suicide, but also as a variable that influences the expression of the suicidal related behaviors. Objective To provide evidence about the effect of religious practices and beliefs on suicidal behavior in cancer patients in Colombia. Methods This is a hospital-based cross-sectional study with a sample of 132 patients with cancer. Socio-demographic data were measured, in which the religious affiliation was included. The instruments used include the Scale of Suicidal Ideation (SSI), the item 9 of Beck Depression Scale (BDI-IA) and the Beck Hopelessness Inventory (BHS). Results In our study, 93% of the patients had advanced stages of cancer, where 51.52% of them were in stage IV. Cancer patients who reported non-Catholic Christians were 3 and 4 times more likely to have some manifestation of suicidal behavior. Conclusions It is recognized in non-Catholic Christians patients a greater chance to express suicidal ideation, which could be related to their level of suicide acceptability. It is considered that religion and their perception of death affects the expression and acceptance of suicidal ideation, reason why it is necessary more research on the effect of different religions on suicidal behavior, in order to include these aspects in the patient intervention. © 2016 Asociación Colombiana de Psiquiatría